Perilaku Komunikasi Remaja Pemain Game Online ‘‘Mobile Legend” - Enelson, Fendi; Putra , Dilmai; Sari , Sapta (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2024)
Currently online games are very popular with almost all groups. Online games are interesting to play, in fact for some people online games have become a primary need. In the past, online games could only be enjoyed via a personal computer (PC), but as time goes by, now online games can be enjoyed anywhere and anytime via smartphone. This research aims to understand teenagers' communication behavior towards the online game "Mobile Legends" in Lubuk Durian Village, Kerkap District, North Bengkulu Regency. In today's digital era, online games have become one of the main forms of entertainment for teenagers, influencing the way they interact and communicate. This research was conducted to explore adolescent communication behavior. The research method used is a case study with a qualitative approach. Primary data was obtained through in-depth interviews and direct observation of teenagers who actively play "Mobile Legends" in the age range of 13 to 20 years. The focus of this research is the analysis of interpersonal communication behavior that occurs in the context of games and how this affects teenagers' social lives, such as the way teenagers communicate with parents and the way teenagers communicate with friends outside the game. The research results show that the use of "Mobile Legends" has various impacts on adolescent communication behavior. On the one hand, this game improves cognitive skills, motor skills and the ability to work together in teams. Teenagers can also expand their social networks and interact with friends from different countries. However, on the other hand, excessive use can cause addiction, disrupt study time, and have negative impacts on mental and physical health, such as anxiety and sleep disorders. This research provides practical insights for parents, educators and game developers in supporting the healthy and productive social and emotional development of teenagers.